TRANSFORMASI KOMPETENSI GLOBAL MELALUI PROGRAM MBKM BERDAMPAK INTERNATIONAL STUDENT EXCHANGE DI WUHAN VOCATIONAL COLLEGE OF SOFTWARE AND ENGINEERING, CHINA - Dwi Nova Catharina Ramadhini Nainggolan; H. Wahyudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) Berdampak International Student Exchange Program is an international learning program aimed at improving students’ academic competence, technical skills, communication abilities, and global insight. This program was conducted at Wuhan Vocational College of Software and Engineering in Wuhan, China. The participants departed on March 26, 2026, and academic activities officially began on March 30, 2026 through an opening ceremony. During the program, students participated in various theoretical and practical learning activities related to industrial technology and automation, including Programmable Logic Controller (PLC), Data Communication Technology, Mechanical Operation Robot, Engineering Computer Graphics, Digital Factory Virtual Simulation, Automotive Wheel Hub Automated Assembly Line, Fundamental of Automatic Control, Physical Education, and Industrial Chinese. In addition to academic activities, students also participated in cultural and international insight development activities. The implementation of the MBKM Berdampak International Student Exchange Program provided benefits in improving academic competence, technical skills, cross cultural communication abilities, and students’ adaptability in an international environment. This program also provided global experience and insight to prepare students for industrial development and global competition.